Influence of Sowing Dates and Nutritional Background on the Formation of the Yield of Winter Rye - Umarov R. A; Azizov B. M (International Journal on Integrated Education, 2021)
Winter rye has an increased competitive ability for survival in agrocenosis - a powerfully developed root system with a high assimilating ability, little damage from pests, relative resistance to diseases, and the ability to withstand stress factors. Well-developed plants tolerate a drop in temperature at the depth of the tillering node to -20, -22 ° C. In the experiment, a relatively low yield of rye grain, 16.2 c / ha, was noted at later sowing dates on November 1 without the use of mineral fertilizers. A relatively high yield of rye grain, 53.3 c / ha, was noted at early sowing dates with the use of a biostimulator (Baykal) against the background of NPK. The increase in the grain yield of winter rye due to the use of biostimulants was 30.0 c / ha.